SPESIES PARASITOID LIPAPHIS ERYSIMI ASAL SUMATERA SELATAN DAN VARIASI PARASITISASINYA PADA TUMBUHAN INANG YANG BERBEDA - Siti Herlinda; Erise Anggraini; Chandra Irsan; Abu Umayah; Rosdah Thalib; Triani Adam (Universitas Lampung, 2012)
Lipaphis erysimi (Hemiptera: Aphididae) is one of the main insect pests on brassicaceous crops. Aphids attack crops by sucking sap from its hosts. Densed population in the initial phase of crop growth could inhibit growing, loss in yield up to 100%. Experiments were aimed to explore and identify species of L. erysimi parasitoid in highland areas of South Sumatra, and to determine potency of the parasitoids to parasitize L. erysimi in laboratory. The highest parasitism level of L. erysimi (72.40%) was found on 200 aphids which reared on B. juncea. While, the second highest parasitism level (65.67%) was found on N. indicum. The number of mummies found on N. indicum was less than on B. juncea. Of all observations, every treatment on every tested plant showed that female D. rapae emerged more than male D. rapae (female bias). The two parasitoids species that parasitized L. erysimi were Diaeretiella rapae and Aphidius sp. Parasitisation at several location in South Sumatera was highly diverse. D. rapae was the most abundant parasitoid species on several high lands at South Sumatera.